Pervious materials for the flood mitigation process in Kuala Lumpur: a review - Md Sahak, Nursah’aidah; Mohd Yunos, Mohd Yazid; Maulan, Suhardi; Ismail, Nor Atiah (Human Resource Management Academic Research Society, 2022)
By locating and examining existing literature on this topic's past research, this study aims to assess the importance of perviousness in reducing flash floods in Kuala Lumpur. The terms perviousness, pervious materials, pervious surface, and flash floods were used in the literature research and identification. The majority of articles are found on environmental and water management websites. Pervious surfaces come in two basic designs. Permeable pavement is the initial design including permeable interlocking concrete pavers and concrete grid pavers. A buffer garden is the second option. However, due to space constraints in urban locations, the permeable pavement has become the preferred method of reducing stormwater runoff. Using permeable pavement has a lot of benefits, but there are some drawbacks to consider. This constraint can be alleviated if all proper methods are used during installation and maintenance. Because the most significant constraint is a lack of competence in permeable pavement technology, technical research on how to manage the right approach to this technology should be produced, covering all important areas from management, planning, site selection, and pervious paving maintenance. This program should include participation from all levels of decision-makers and stakeholders, as well as civil society.